Diversity of flower‐visiting hoverflies (Diptera: Syrphidae) on ground cover vegetation from the market‐gardening area of Meskine (Far‐North Region, Cameroon). (23rd August 2021) - Azo'o Ela, Michelson; Bissou Wangbara, Bernard; Jordaens, Kurt
Abstract: We characterised the hoverfly (Diptera: Syrphidae) community on ground cover vegetation in the market garden of Meskine (Far‐North region of Cameroon). Hoverflies were collected by hand‐netting from flowers of ground cover vegetation in 20 grass strips from March to June in two consecutive years (2017–2018). In total, 15 hoverfly species were collected of which eight were new to Cameroon (subfamily Eristalinae: Eristalinus megacephalus, Eristalinus tabanoides, Eristalinus aff. arvorum, Phytomia curta, Phytomia pallida, Phytomia incisa, Mesembrius caffer ; subfamily Syrphinae: Asarkina sp.). The subfamily Eristalinae was most abundant (74% of the specimens collected), while species of the subfamily Syrphinae accounted for 26% of the occurrences. Four species were extremely abundant ( M .  caffer, E .  tabanoides, E . aff. arvorum and Paragus borbonicus ) accounting for 70% of all flower visit observations, while the other species were rarer. Plant species with yellow or white flowers seemed to be most attractive. Hoverfly activity was high in the morning and evening and decreased at noon, most likely due to the higher air temperature and lower humidity during this period. The characterisation of hoverfly communities and the management of wild flower strips surrounding cultivated fields could be an important practice to improve crop pollination by hoverflies. Résumé: Nous avons caractérisé la communauté de syrphes (Diptera: Syrphidae) en fonction de la couverture végétale des sols de la zone maraîchère de Meskine (située dans l'extrême‐nord du Cameroun). Les syrphes ont été collectés au filet de piégeage entre mars juin sur les fleurs présentes dans la couverture végétale de 20 bandes enherbées pendant deux années consécutives (2017 et 2018). Au total, 15 espèces de syrphes ont été collectées. Huit d'entre elles étaient nouvelles au Cameroun (sous‐famille Eristalinae: Eristalinus megacephalus, Eristalinus tabanoides, Eristalinus aff. arvorum, Phytomia curta, Phytomia pallida, Phytomia incisa, Mesembrius caffer ; sous‐famille Syrphinae: esp. Asarkina ). La sous‐famille Eristalinae était la plus abondante (74% des spécimens collectés), tandis que les espèces de la sous‐famille Syrphinae représentaient 26% des syrphes présents. Quatre espèces étaient extrêmement abondantes ( M . caffer, E . tabanoides, E . aff. arvorum et Paragus borbonicus ) et représentaient 70% de toutes les visites de fleurs observées, tandis que les autres espèces étaient plus rares. Les espèces végétales à fleurs jaunes ou blanches semblaient être les plus attrayantes. L'activité des syrphes était élevée le matin et le soir et diminuait à midi, très probablement en raison de la température de l'air plus élevée et de l'humidité plus faible pendant cette tranche horaire. La caractérisation des communautés de syrphes et la gestion des bandes de fleurs sauvages entourant les champs cultivés pourraient devenir une pratique essentielle visant à améliorer la pollinisation des cultures par les syrphes.